1992
DOI: 10.1136/bmj.304.6834.1093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feedback on test ordering behaviour of general practitioners.

Abstract: Objective-To assess the effects of feedback on the test ordering behaviour of general practitioners.Design-Comparison of requests at two diagnostic centres, and internal comparison between tests which were discussed in feedback and tests which were not.Setting-A diagnostic centre in Maastricht giving feedback and another elsewhere in the Netherlands (laboratory A) not giving feedback.Subjects-All 85 general practitioners in the region of Maastricht, and all general practitioners in the region of laboratory A.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 11 publications
0
25
0
1
Order By: Relevance
“…Information was transmitted to the physicians in various forms, as suggested by Solomon et al (8 ), Valenstein (7 ), and Grimshaw et al (21 ). Our education and feedback information was personalized as extensively as possible and included a form of peer pressure, which could have a strong influence over physician behavior (14,(17)(18)(19). Finally, there were multiple visits over the approximately 2 years of the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Information was transmitted to the physicians in various forms, as suggested by Solomon et al (8 ), Valenstein (7 ), and Grimshaw et al (21 ). Our education and feedback information was personalized as extensively as possible and included a form of peer pressure, which could have a strong influence over physician behavior (14,(17)(18)(19). Finally, there were multiple visits over the approximately 2 years of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies within the Harvard Community Health Plan were associated with a highly academic facility. The approach of the Winkens group is resource-intensive (17)(18)(19), and beyond the scope of most nonacademic communities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that following the introduction of individual feedback to general practitioners on their use of diagnostic tests, there has been a decrease in the number of requests for tests. 27,28 Providing feedback for the PCPs in this center on their high diagnostic accuracy and pointing out which cases they deemed to be diagnostically inadequate may direct attention to the type of cases requiring diagnostic referrals to the neurology outpatient clinic. The possibility of neurologists holding outpatient clinics in community settings can also be increased.…”
Section: Discussionmentioning
confidence: 99%
“…5 There is evidence that rapid access to those results is a costeffective means of improving the appropriateness of the requests for laboratory investigations. 6,7 The Grampian study of a guideline-based open access urological investigation service demonstrated improved patient waiting times when appropriate investigations were ordered and reviewed by GPs. 8 A systematic review by a group in Boston, USA showed that feedback of …”
Section: Introductionmentioning
confidence: 99%